Artikel Review: Teknologi Zeolit untuk Penangkapan Karbon (Carbon Capture): Karakteristik, Modifikasi dan Tantangan Operasional - Hasrul, Hasrul; Syahwardini, Trisuciati; Wali, Abdul Rahman; Purfaji, Purfaji; Wiranata, Arya; Primarista, Ni Putu Vidya (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Zeolites are promising adsorbents for CO₂ capture due to their high surface area, thermal stability, and cost-effectiveness. Their performance can be enhanced through chemical modifications such as amine impregnation, cation exchange, and hydrophobic surface grafting, enabling improved selectivity and resistance to moisture. However, operational challenges remain, including water competition, regeneration energy demand, and cyclic stability under industrial conditions. Strategies like guard beds, hydrophobic zeolites, and hybrid systems are being developed to overcome these limitations. Zeolite-based adsorption offers a sustainable pathway for reducing CO₂ emissions and advancing low-carbon technologies.